The Immunomodulatory Metabolite Itaconate Modifies NLRP3 and Inhibits Inflammasome Activation - Hooftman, Alexander; Angiari, Stefano; Hester, Svenja; Corcoran, Sarah E.; Runtsch, Marah C.; Ling, Chris; Ruzek, Melanie C.; Slivka, Peter F.; McGettrick, Anne F.; Banahan, Kathy; Hughes, Mark M.; Irvine, Alan D.; et al. (Cell metabolism, 2020)
The Krebs cycle-derived metabolite itaconate is highly upregulated in inflammatory macrophages and exerts immunomodulatory effects through cysteine modifications on target proteins. The NLRP3 inflammasome, which cleaves IL-1β, IL-18, and gasdermin D, must be tightly regulated to avoid excessive inflammation. Here we provide evidence that itaconate modifies NLRP3 and inhibits inflammasome activation. Itaconate and its derivative, 4-octyl itaconate (4-OI), inhibited NLRP3 inflammasome activation, but not AIM2 or NLRC4. Conversely, NLRP3 activation was increased in itaconate-depleted Irg1−/− macrophages. 4-OI inhibited the interaction between NLRP3 and NEK7, a key step in the activation process, and “dicarboxypropylated” C548 on NLRP3. Furthermore, 4-OI inhibited NLRP3-dependent IL-1β release from PBMCs isolated from cryopyrin-associated periodic syndrome (CAPS) patients, and reduced inflammation in an in vivo model of urate-induced peritonitis. Our results identify itaconate as an endogenous metabolic regulator of the NLRP3 inflammasome and describe a process that may be exploited therapeutically to alleviate inflammation in NLRP3-driven disorders. [Display omitted] •Itaconate and its derivative 4-OI (which generates itaconate) block NLRP3 activation•Itaconate-depleted Irg1−/− BMDMs exhibit increased NLRP3 inflammasome activation•4-OI “dicarboxypropylates” C548 on NLRP3 and blocks the NLRP3-NEK7 interaction•4-OI reduces peritonitis in vivo and blocks IL-1β release from CAPS patient PBMCs Hooftman et al. reveal a role for the Krebs cycle-derived metabolite itaconate in regulating the NLRP3 inflammasome. Itaconate specifically blocks NLRP3 inflammasome activation by reducing the NLRP3-NEK7 interaction, likely due to modification of C548 on NLRP3. Furthermore, itaconate inhibits IL-1β release from cells isolated from patients with the NLRP3-mediated disease CAPS.